Akademisk vardag på en global referensmarknad - Sundin, Olof (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2014)
Scholarly literature is integrated into the fabric of scholars’ everyday life. The literature serves both the purpose of communicating content and of constructing the trustworthiness of research and establishing distinctions between scholars. New digital tools, such as Google Scholar or Research Gate, act as filters, yet they also influence and reshape the way people search and publish. As scholars, we need to be aware how these new filters function, and in what ways they answer to contemporary audit culture which emphasizes visibility and productiveness.